Perceived Risk Factors and Foreign Direct Investment Inflows in Nepal’s Hydropower Sector: A Quantitative Analysis - Pandey, Janak Prasad (Journal of Multidisciplinary Research Advancements, 2026)
Nepal possesses an estimated hydropower potential of 83,000 MW, yet less than 3,000 MW has been developed, largely due to financing constraints. Foreign Direct Investment (FDI) has been identified as a critical source of capital, but foreign investors face multiple risk factors—environmental, financial, and economic—that may influence investment decisions. This study quantitatively examines the relationship between perceived environmental, financial, and economic risk factors and FDI inflows in Nepal’s hydropower sector. Primary data were collected from 30 stakeholders in the Kathmandu Valley, including representatives of FDI-based hydropower companies, government authorities, commercial banks, and independent professionals, using a structured 5-point Likert-scale questionnaire. Descriptive statistics, Pearson correlation, and multiple regression analysis were employed. The findings reveal that while stakeholders perceive moderate-to-high levels of environmental (mean = 3.70), financial (3.51), and economic (3.91) risks, they simultaneously report strongly positive perceptions of actual FDI inflows (mean = 4.44). Correlation analysis showed no statistically significant relationship between any risk factor and FDI inflows (p > 0.05 for all). Multiple regression explained only 1.9% of the variance (R² = 0.019) and was not statistically significant (F = 0.157, p = 0.924). None of the three risk factors significantly predicted FDI inflows. Financial and economic risks were significantly correlated (r = 0.570, p < 0.01), indicating their interdependence. The study concludes that perceived environmental, financial, and economic risks do not determine FDI inflows in Nepal’s hydropower sector. Instead, opportunity-driven factors—such as hydropower potential, regional electricity trade prospects, and investment incentives—appear to outweigh risk considerations. Policymakers should focus on enhancing sectoral opportunities rather than solely mitigating perceived risks.